A Tribute to Dr George Barton - Richardson, Ivor LM (Victoria University of Wellington Law Review, 2012)
This address was given by Sir Ivor Richardson on the occasion of the special sitting of the High Court in Wellington on Wednesday 6 July 2011 to honour Dr George Barton QC.